Composition of two‐week change in body weight under unrestricted free‐living conditions. Issue 13 (4th July 2017) - Bhutani, Surabhi; Kahn, Eva; Tasali, Esra; Schoeller, Dale A.
Abstract: The composition of weight change has a large impact on energy balance calculations. Composition of long‐term weight change interventions is well‐documented, but information on short‐term weight change under unrestricted free‐living conditions is limited. The composition and energy density of the changes in body weight during 2‐week free‐living conditions were analyzed in adults from two cohorts: cohort 1 ( n  = 24) included participants from the reproducibility subset of the Observing Protein and Energy Nutrition study; cohort 2 ( n  = 22) included participants who were studied under free‐living conditions in an ongoing study in the Chicago area. Change in body weight, total body water (TBW) by stable isotope dilution (cohort 1), and fat mass (FM) and fat‐free mass (FFM) by serial DXA (cohort 2) were measured. To determine the fractional composition of the change in body weight we analyzed the linear associations between changes in body weight and changes in body composition. In the combined dataset, the average change in body weight (0.26 ± 1.2 kg) was consistent with being in energy balance. Average change in body weight was associated with the change in TBW ( P  < 0.0001) in cohort 1 and the change in FFM ( P  = 0.0002) in cohort 2. A unit change in body weight was composed of 84% change in FFM in the combined dataset indicating that 2‐week fluctuation in body weight is largely composed of FFM. The energy density of 1–3 kg short‐term changes in body weight averaged 2380 kcal/kg. Abstract : Little data is available on the tissue composition and hence energy density of short‐term fluctuations in body energy stores weight. Here we report a relatively larger contribution of fat‐free mass (84%; mainly body water), as compared to fat mass (16%), to the body weight fluctuations after 2‐weeks of unrestricted free‐living conditions. We also show that the energy density of short‐term changes in body energy stores is small. Our findings are useful for short‐term, near energy balance studies where body composition cannot be easily measured.